Aptamer-based diagnostics and therapeutics in viral sepsis: current progress, application and future prospects - Noraini Abd-Aziz; Fatimah Ibrahim; Sun Tee Tay (Current Research in Biotechnology, 2025)
Sepsis is a systemic inflammatory response to microbial infection that is characterized by a spectrum of physiological and pathological disorders. Viruses have been identified with varying roles in the context of sepsis. Diagnosing viral sepsis poses a great challenge due to a lack of viral detection reagents and assays, contributing to the underreporting of prevalence. Aptamers are single-stranded nucleic acids (either DNA or RNA) that can fold into specific structures, enabling their binding with a wide array of target molecules with high affinity and selectivity. This review provides updates on advances in aptamer development for viruses implicated in sepsis, aptamer selection methodologies through Systematic Evolution of Ligands by Exponential Enrichment (SELEX), and application of aptamer-based diagnostics and therapeutics. Additionally, several critical challenges in aptamer technology are addressed, with special emphasis on its analytical sensitivity, functional complexity, and translation to clinical practice.